Study of possibilities to grow biofortified vegetables as a source of cаrotenoids - Дейниченко, Григорій Вікторович; Юдічева, Ольга Петрівна (Eastern-European Journal of Enterprise Technologies, 2015)
Micronutrient deficiency significantly affects the nutritional status and population health in both well-developed and developing countries. This deficiency causes growth inhibition in children, various diseases, mortality, brain damage, reduced cognitive abilities and working capacity of people of all ages. The global prevalence of micronutrient deficiency in the food ration, including vitamin A deficiency has led to the action program development to mitigate the negative effects of micronutrient malnutrition. Solving the problem by implementing biofortification and fortification strategies in our country is aimed at reducing specific deficiencies of iron, zinc and vitamin A in the food ration, especially of people with low living standards. Biofortification in growing vegetables is one way to increase the content of important minerals and vitamins, which in turn affects the food ration balance. A study of carotenoid content in different varieties of eggplant, sweet pepper, pumpkins and melons was performed. The studied samples of vegetables were grown using environmentally friendly fertilizer "Riverm", which provides a natural increase in the content of vitamins and minerals in vegetables (agronomic biofortification) and control samples - using traditional growing technology. The research results allow to conclude that the carotenoid content in agronomically biofortified vegetables that have been grown using environmentally friendly liquid fertilizer "Riverm" exceeds the carotenoid content in control samples. In particular, the studied eggplant samples contained by 27% more carotenoids than vegetables grown by traditional technology. Oleshkivskiy pumpkins that have been grown with fertilizer "Riverm" had by 22.8% higher carotenoid content than in control samples. The studied melon samples contained by 23,3-26,9% more carotenoids than the control samples. Thus, biofortified vegetables can be used in special micronutrient diets and, along with fortified food, can be used to solve the micronutrient malnutrition problem.